Andrea McGuire interviews Joey Yard, Witless Bay. - McGuire, Andrea (2014)
Andrea McGuire interviews Joey Yard about the writing he does in his Witless Bay shed. 00:56 - Uncertainty about continuation of interview; 02:45 - Shed writing about Cod Moratorium, 1992; rewriting the text for emphasis; 03:30 - Writing on walls of shed to remember events, names; 03:40 - Shed writing about "Cod War" between Spain and Canada, 1995; Brian Tobin; John Crosbie; Richard "Ricky" Cashin; 04:01- Shed writing to commemorate death of cat, Cuddles, in May 2010; 04:20 - Shed writing as a social activity; initiated by visitors; 04:36 - Shed writing restricted to just one of six sheds on property; 04:56 - Other shed writing in community unknown to interviewee; 05:11 - Appreciation for aesthetic of shed writing; Interviewee "wouldn't tear down" the shed; 05:35 - "You wouldn't forget" the cod moratorium; 05:45 - Shed writing to chronicle important events; 06:06 - Perspective on future of cod fishery; 06:45 - Shed writing during son's parties; 07:16 - Visitors write their names, but other writing done by interviewee; 08:21 - Interviewee remembers everything to do with the fishery; 08:36 - Shed writing to record weather events; 09:00 - Discussion of other shed writing in Witless Bay; 09:54 - Frequency of shed writing; 10:21 - Framed images in interviewee's shed; 11:45 - Shed writing as compared with journal writing; 12:40 - Written warning, "Enter at Own Risk" on shed door